Jip : his story - Paterson, Katherine (New York : Lodestar Books, 1996)
While living on a Vermont poor farm during 1855 and 1856, Jip learns his identity and that of his mother and comes to understand how he arrived at this place.
Keywords: Slavery -- United States -- Fiction